Increased prevalence of imprinting defects in patients with Angelman syndrome born to subfertile couples. Issue 4 (1st April 2005) - Ludwig, M; Katalinic, A; Groß, S; Sutcliffe, A; Varon, R; Horsthemke, B
Abstract : Recent case reports have suggested that infertility treatment with intracytoplasmic sperm injection (ICSI) may increase the risk of imprinting defects leading to Angelman syndrome (AS). Although imprinting defects account for only 4% of patients with AS, we have found four cases among 16 AS patients born to subfertile couples, who conceived with or without infertility treatment (25%; relative risk (RR) 6.25; 95% confidence interval (CI) 1.68 to 16.00). The risk in untreated couples with time to pregnancy (TTP) exceeding 2 years was identical to that of those treated by ICSI or by hormonal stimulation alone (RR 6.25; 95% CI 0.70 to 22.57). It was twice as high in couples who had received treatment and also had TTP >2 years (RR 12.5; 95% CI 1.40 to 45.13). Our findings suggest that imprinting defects and subfertility may have a common cause, and that superovulation rather than ICSI may further increase the risk of conceiving a child with an imprinting defect.